Navigating the Liminal Identity of Various Characters in the Novels of Hala Alyan - Limba, Reetu; Pandey, Sanjay Prasad (Journal of Neonatal Surgery, 2025)
Identity is a multifaceted concept encompassing the unique characteristics, beliefs, and affiliations that define an individual or group. It serves as a lens through which people perceive themselves and are recognized by others, evolving through personal experiences, social interactions, and cultural contexts. Liminal identity refers to being “in-between” or on the threshold of two or more identities, cultures, or social positions. This concept is rooted in the idea of liminality, which describes a transitional phase or space where individuals experience ambiguity, uncertainty, or transformation. A liminal identity often emerges when a person occupies a space between different identities or roles. This paper examines the recurring theme of liminal identity in Hala Alyan's novels, focusing on how her characters embody the "in-between" state of cultural, social, and personal identities. This paper has been written by using qualitatively deductive methodology. The theory of liminality by Arnold van Gennep and Victor Turner has been used to analyse Hala Alyan's novels, Salt Houses and The Arsonists' City to trace liminal identity, particularly within displacement, migration, and cultural hybridity. These works explore the lives of Palestinian families navigating the complexities of exile, belonging, and identity across generations.